Dynamics of Intergenerational Transmission of Traditional Agricultural Knowledge in the Dayak Kenyah Community: Challenges and Opportunities for Strengthening Ethno-Sciences in the Modern Era - Ibrahim, Riza; Yuningsih, Siti Hadiaty (International Journal of Ethno-Sciences and Education Research, 2025)
In an era of increasingly rapid modernization, the sustainability of TAK faces serious challenges, ranging from rural-urban migration, formal curricula that ignore local content, and declining interest among the younger generation in agricultural practices based on local wisdom. Using a qualitative ethnographic approach, this study uncovers inheritance patterns, transmission channels, inhibiting factors, and potential for revitalization. The results indicate a generational gap, with elders still maintaining knowledge retention rates above 90%, while younger generations retain only around 25%. Nevertheless, opportunities for revitalization emerge through community initiatives, the integration of TAK into local curricula, and the development of technology-based agroecological entrepreneurship. This study confirms that cross-generational collaboration, policy support that recognizes the value of local knowledge, and the synergy between tradition and innovation are key to TAK's sustainability. Thus, TAK is not only a cultural heritage, but also a strategic resource for food security, biodiversity conservation, and strengthening the ecological identity of indigenous communities in an era of socio-ecological change.